Information aspect and proposals for improving approaches to overcoming the sociogenic consequences of a radiation-dangerous emergency - Borisevich Н. Я.; Lupey О. В. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
In the article there has been given the analysis of information supply of the population, living on the territories contaminated by radionuclides.